Photography in dentistry: Part III (Dental portraits) - Mirfazaelian A.; Siadat H. (Tehran University of Medical Sciences, 2006)
Dental portraits are predominantly used for orthodontics, orthognathic surgery and prosthetic dentistry. If these images are to be used for documentation, then the patient must be positioned in accordance with strict guidelines for further references. If the images are to be used to present an aesthetic impression of dental treatment there is more flexibility in positioning the patient. Dental photography is used to make pictures of teeth and surrounding tissues, radiographs, casts and other objects. In this section, standard principles for portrait pictures are explained.